INTERVENSI KEPERAWATAN SENAM KAKI DIABETIK UNTUK PENCEGAHAN ULKUS KAKI DIABETIK PADA PASIEN DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS MASOHI - ACHMAD, IRHAMDI; Resiloy, Jesicha; Imran, Andi Miftahul Khair; Ohorella, Usman Barus; Metekohy, Feby Adolf (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2024)
Increasing prevalence of type II diabetes mellitus (DM) leads to various complications, including diabetic foot ulcers, which can risk amputation. Diabetic foot exercise nursing intervention is considered effective as a preventive measure. This study aims to describe the implementation of this intervention in the Masohi Community Health Center. Using a case study design, the subjects included two patients with type II DM for 5-10 years. Data collection involved interviews, vital sign measurements, and diabetic foot ulcer risk assessment using Inlow's 60-Second Diabetic Foot Screening Tool before and after the intervention. The results showed that the first subject experienced a reduction in diabetic foot ulcer risk scores from 8 to 6 on the left foot and from 5 to 3 on the right foot, alongside a decrease in random blood glucose levels (GDS) from 387 mg/dL to 255 mg/dL. For the second subject, the ulcer risk score decreased from 5 to 3 on the left foot and from 8 to 6 on the right foot, with GDS dropping from 339 mg/dL to 250 mg/dL. These findings indicate that diabetic foot exercise effectively reduces ulcer risk and aids in blood glucose control. This study is expected to provide a reference for community health centers and educational institutions in implementing diabetic foot exercise nursing interventions for the prevention of diabetic foot ulcers in type II DM patients.